Speed studies on Malaysia East Coast expressway - Wahyu Nur Susianna, Omar (2017)
Road accidents is one of a serious issue. Every year the number of accidents that occur was increase relatively despite variety of efforts have been made to reduce accidents. Speeding might be one of the greatest contributor factor of road accident compared to the other factors. The purpose of this study was conducted is to obtain vehicle speed at a point along a straight road. Besides that, the level of compliance of the driver to the speed limit will also be evaluated. The study was conducted using a radar gun to obtain the local speed data for the selected location. The selected location is on east coast expressway phase 1 KM 164.6 which is 500meter before the warning sign and KM 163.6 which is 500meter after the warning sign, while the east coast expressway phase 2 is at KM273 where from the police report statistic, the number of accident are higher for that road. The observation results of the spot speed data was analysed using statistical graph of the distribution histogram, the distribution of local speed and distribution graphs of frequent incremental. The results of this study found that the level of compliance of drivers to the speed limit is very low with the percentage of drivers who drive exceeding the speed limit is very high.